Evaluation and Comparison Anti-aging Facial Serum from Algae Extract - Permadi, Adi; Aziz, Abdul; Ramadani, Noorpani; Nazzal, Sami; Maryudi, Maryudi; Suharto, Totok Eka (Universitas Ahmad Dahlan, 2023)
The demand for cosmetics in Indonesia is quite high so cosmetics can now be said to be a primary need. Therefore, various cosmetic products have emerged that are cheap and provide instant results but ignore the health aspects of the user. Several cosmetic products make a breakthrough by using natural ingredients. One natural material that can be used is microalgae which can produce bioactive compounds and has a relatively faster production process compared to other natural materials. In this research, the microalgae used were Chlorella sp. and Spirulina sp., and Sargassum sp. This research aims to make a serum based on the Chlorella sp., Spirulina sp. and Sargassum sp. microalgae. The research results showed that the standard testing of simplicial facial serum extracts of Spirulina sp., Chlorella sp., and Sargassum was by SNI No. 16-4399-1996.[ASUS1] [AP2] All the metrics analyzed, such as organoleptic characteristics, pH, specific gravity, viscosity, active compounds, and microbiological contamination, have successfully fulfilled the required requirements in SNI no. 16-4399-1996.. The results of antioxidant activity testing showed that Chlorella sp. had higher antioxidant activity than the other three types of samples. However, the antioxidant results obtained are still very low and relatively weak, which means this serum does not fully contribute to antiaging. Further research needs to be carried out to obtain serum from microalgae with high levels of antioxidants, including by using fresh simplicia, elevated algae concentration or optimizing the operating conditions. [ASUS1]Please add short information about the main results, whether the serum satisfies the standard or not, which parameters, etc. [AP2]Has been added